Peran Self Efficacy, Soft Skill, Dan Hard Skill Terhadap Peningkatan Kesiapan Kerja Bagi Mahasiswa Tingkat Akhir Fakultas Ekonomi Universitas Negeri Gorontalo - Podungge, Robiyati; Bokingo, Agus Hakri; Hilala, Exzalin (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to determine how much influence Self Efficacy, Soft Skills, and Hard Skills have on the work readiness of final students of the economics faculty, State University of Gorontalo (study of final semester students class of 2019). The sampling technique taken in this study used non-probability sampling, the number of samples taken in the study used the slovin formula, namely 100 respondents. The data collection technique in this study used a questionnaire with a population of students from the 2019 class of the Faculty of Economics, Gorontalo State University. The analytical test tool used in testing this research is multiple linear regression. The results showed that the results of the Self Efficacy test had a significant positive effect on work readiness, Soft Skills and Hard Skills had an insignificant positive effect on student work readiness. The variables of Self Efficacy, Soft Skill and Hard Skill in explaining the work readiness variable are 61.5% while the remaining 38.5% are influenced by other variables not examined and explained in this study. Keywords: Self Efficacy, Soft Skill, Hard Skill